Inclusion of venture capital to improve the welfare of female headed households in South Jakarta - Ilham Mundzir; Ririn Fitria Nilamsari; Falah Kurniaharnoto; Nabilah Nur Fajrina; Refinda Fionita; Nabila Muthia Khansa; Farah Syifa Aulia (Universitas Muhammadiyah Magelang, 2021)
This community service activity is focused on helping women from poor families to be able to revitalize their businesses affected by the Covid-19. Poverty in women's groups, especially female headed household has become one of the top global agenda. However, the Covid-19 pandemic has resulted that these groups becoming poorer, not least in Jakarta, Indonesia. Therefore, this community service is focused on efforts to uplifting their economy by providing capital to set up small business. Youth Participatory Action Research (Y-PAR) is used as the community service approach, collaboration of lecturers and students. This service activity has been able to encourage poor women who previously lost their income, managed to regain their economic resources and create new businesses to improve the welfare of their families.